CERITA RAKYAT SUKU DAYAK RANDUK STRUKTUR DAN NILAI BUDAYA - Tirsa, Aprima; Effendy, Chairil; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract       The problem of this study is focused on the foklore of the Dayak Randuk tribe (cultural structure and value). The purpose of this study describes the structure and cultural value contained in the foklore of the Dayak randuk tribe.This research uses descriptive methods with the form of the research is qualitative. The sources of the research are from the set of foklore stories of Dayak Randuk. They are stories that have been researched they are (1) teks Nyntak Nyuntai, (2) teks Legenda Batu Randuk, (3) teks Raja Deah, (4) teks Cit Inai, (5) teks Raja Kancil. The structure contain inthe stories, plot, story figure (charakter is story) background and theme. The cultures value the consisted in the foklore of Dayak Randuk include the view of nature and view of another.       Keyword: foklore, structure, culture value.